2014
DOI: 10.1002/app.41181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poly(ethylene glycol) on the properties and foaming behavior of macroporous poly(lactic acid)/sodium chloride scaffold

Abstract: In this study, we prepared poly(lactic acid) (PLA)/poly(ethylene glycol) (PEG)/sodium chloride (NaCl) blends by melt blending with a triple‐screw dynamic extruder. The effects of PEG on the thermal property, mechanical property, and morphology of blends were investigated in detail. It was found that the incorporation of PEG and NaCl significantly improved the crystallization rate, elongation at break, surface adhesion, and reduced viscoelasticity of PLA. The blends were further batch‐foamed at different temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
(43 reference statements)
2
16
0
Order By: Relevance
“…Consistent with a previous report [40], rinsing out water-soluble PEG is in favor of improving pore interconnectivity (Figure 3b). All the porous PLA scaffolds exhibit high connectivity in excess of 97%.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with a previous report [40], rinsing out water-soluble PEG is in favor of improving pore interconnectivity (Figure 3b). All the porous PLA scaffolds exhibit high connectivity in excess of 97%.…”
Section: Resultssupporting
confidence: 92%
“…An integrated structure is a necessary prerequisite for PLA scaffolds to prevent premature collapse and to promote bone tissue regeneration in vivo . As evidenced by the existing literatures, inclusion of NaCl component depresses the chain mobility of PLA and results in inferior flowability [40]. Our preliminary exploration also found that there were visible cracks on the surface of PLA/NaCl extrudates; subsequently, the binary blends collapsed irreparably during the leaching process due to structural defect.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…This is due to its high costs related to complicated screw geometry and barrel construction, comparing to single-or twin-screw extruders. Nevertheless, recently triple screw extruders were successfully applied for preparation of biobased materials, such as microcellular poly(lactic acid)/talc biocomposites [38], poly(lactic acid)/poly (vinyl alcohol) blends [39] or poly(lactic acid)/poly (ethylene glycol) porous scaffolds [40][41][42]. In our opinion, application of triple-screw extrusion during reactive extrusion of 'conventional' and biodegradable polymers will be developing in near future.…”
Section: Extruders As Chemical Reactors -Basic Conceptsmentioning
confidence: 99%
“…PLA based nanocomposites, which include PLA based copolymers in nanometer size and nanocomposites with PLA or PLA copolymers as matrix and nanofillers as annexing agent, have shown great potential in biomedical field [26]. The small scale effect and surface effect nanomaterials have particularly helped improve the properties of PLA and make PLA based nanocomposites more popular compared with pure PLA materials when it comes to synthetic bone substitute and repair, tissue engineering, and drug delivery system.…”
Section: Introductionmentioning
confidence: 99%